GSK343 modulates macrophage M2 polarization through the EZH2/MST1/YAP1 signaling axis to mitigate neurological damage induced by hypercalcemia in CKD mice - Cao, Yaochen; Sun, Hongming; Li, Xitong; Pommer, Wolfgang; Xiong, Yingquan; Chen, Xin; Chu, Chang; Yu, Fabiao; Hocher, Berthold; Wang, Ziqiang (Cellular signalling, 2024)
Chronic kidney disease (CKD) often culminates in hypercalcemia, instigating severe neurological injuries that are not yet fully understood. This study unveils a mechanism, where GSK343 ameliorates CKD-induced neural damage in mice by modulating macrophage polarization through the EZH2/MST1/YAP1 signaling axis. Specifically, GSK343 downregulated the expression of histone methyltransferase EZH2 and upregulated MST1, which suppressed YAP1, promoting M2 macrophage polarization and thereby, alleviating neural injury in hypercalcemia arising from renal failure. This molecular pathway introduced herein not only sheds light on the cellular machinations behind CKD-induced neurological harm but also paves the way for potential therapeutic interventions targeting the identified axis, especially considering the M2 macrophage polarization as a potential strategy to mitigate hypercalcemia-induced neural injuries.